PERENCANAAN GROUND SILL DI SUNGAI SENJOYO KABUPATEN SEMARANG - Ichwan Rachmat Putra; Imam Adi Prabowo; Sri Eko Wahyuni; Al Falah (Jurnal Karya Teknik Sipil, 2015)
Senjoyo River is a tributary of Tuntang River which are ±138 km2catchment area, 37 km length and 0,008 bottom slope. That condition causes scour at the bridge foundation. The location of bridge is in Tempuran Village, Bringin Subdistric, Semarang Regency. The solution to conserve the Senjoyo River has to build a ground sill. Ground sill is building cross river which is built to protect degradation in the upstream of river. The ground sill analysis is needed hydrologic analysis to calculate the design flood discharge, hydraulic analysis to calculate the passing capacity discharge, analysis of sediment transport and riverbed’s stability to calculate the value of stable slope and bank protection, hydraulic analysis to compute the dimension of new river, slope stable analysis to calculate the riverbank slope which is stable and the design of ground sill to calculate the dimension of ground sill, stilling basin and bottom protection. The conclution of ground sill design is 2 m ground sill height, 62 m ground sill width, 16 m stilling basin length and 20 m bottom protection length. The conclution of river normalization is 0,00024 stable slope, 120 m new river width and 1:1 riverbank slope. The ground sill can protect the foundation bridge and can be increase the river bottom level until the existing of river bottom level before degradation.